PENGEMBANGAN MANAJEMEN PENGELOLAAN POSYANDU REMAJA MENUJU TALENTA MUDA INDONESIA EMAS 2045 DESA SEHAT BULANGKULON GRESIK - Safara, Anggik Firda; Jumati, Nurleila; Nazarudin, Faisal Fikri; Rachmania, Risca Ayu; Azizah, Nur Aini; Budi Sari Wulan, Dyah Puspita Indah (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2024)
Golden Indonesia 2045 marks a historic moment when Indonesia age reaches 100 years. The Minister of PANRB noted that the country will experience a demographic bonus with 70% of productive age population and 30% of non-productive age. The demographic peak bonus is estimated to occur in the 2030s, where 68% of Indonesia's population will be productive age. This opportunity demands an important role from the younger generation, which is expected to bring positive changes to Indonesia. Adolescence is a unique period, namely the transition period for children to adulthood. Physically they are healthy, but there are several groups who have emotional risks and free associations such as smoking, alcohol, health problems, sexuality, violence, and so on. Bulangkulon Village located in Benjeng District, Gresik Regency is not free from adolescent health problems, one of which is that there are several adolescents who experience serious health problems including stroke, hypertension, cholesterol, gout, and kidney failure and even death. The purpose of community service activities is to increase the effectiveness of Karang Taruna Prabumerjaya Youth Posyandu organization with the Development of Youth Posyandu Management in Bulangkulon Village by the cadre formation of Bulangkulon Village Posyandu members and to improve the quality of healthy life of Bulangkulon Village teenagers. The methods used in community service activities include: a) preparation stage, b) implementation of training stage for Youth Posyandu cadres and Karang Taruna Prabumerjaya to be able in using health equipment and c) evaluation stage. The results is cadres to be able to implement the use of health equipment directly in checking the physical health of teenagers in Bulangkulon Village. It is hoped that for the sustainability of Youth Posyandu cadre program, it can continue to regenerate and develop by involving the village, Ponkesdes and the entire Bulangkulon Village community.